PELATIHAN DAN PENDAMPINGAN PENGUATAN KAPASITAS USAHA DAN LEGALITAS UMKM DESA WRINGINSONGO KABUPATEN MALANG - Sapto Wibowo; Evi Suwarni; Ratna Ika Putri Ika Putri; Muhammad Akhlis Rizza (P3M Politeknik Negeri Malang, 2025)
This community service program aims to strengthen business capacity and legal compliance of Micro, Small, and Medium Enterprises (MSMEs) in Wringinsongo Village, Malang Regency. The main problems faced by the partners are the lack of knowledge among MSME actors regarding business licensing, product certification, and business administration, which limit their market access and competitiveness. The program was carried out by the community service team of Politeknik Negeri Malang in collaboration with the Office of Cooperatives and Micro Enterprises of Malang Regency. The methods included training sessions, interactive discussions, and technical assistance in managing business legality, such as Business Identification Number (NIB), Home Industry Food Permit (PIRT), halal certification, and trademark registration. The activity involved 30 MSME participants from Wringinsongo Village on August 14, 2025. The results show an increased understanding and awareness of the importance of business legality, as well as practical skills in managing legal documents. Moreover, this activity fostered a collaborative network between MSMEs and the local government, ensuring long-term sustainability of the enterprises. With this assistance, MSMEs in Wringinsongo Village are expected to grow more competitively, achieve higher business professionalism, and contribute to local economic development.